1988
DOI: 10.2337/diacare.11.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gestational Diabetes and Macrosomic Newborns in a Mexican Population

Abstract: Prevalence of gestational diabetes was investigated in 693 pregnant patients between the 24th and 28th wk of gestation. A glucose screening test (GST) was performed with a 50-g glucose load, followed by a blood sample 1 h later. Patients with glucose levels greater than 140 mg/dl 1 h after the GST were scheduled for a full oral glucose tolerance test (OGTT). One hundred seven patients had an abnormal GST, and 30 patients (4.3%) were diagnosed as having gestational diabetes mellitus (GDM). The percentage of GDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
0
7
0
4
Order By: Relevance
“…Although no significant differences between groups were found, e.g., for proportions of cesarean sections, CPD, or fetal distress, it may be that sample sizes in this study were inadequate to detect small differences. Jovanovic and Peterson (12), Frisoli et al (13), Forsbach et al (14), and Leiken et al (15) have shown that a high percentage (12-28%) of women with abnormal 50-g 1-h glucose challenge tests but normal 3-h OGTTs have babies weighing >4000 g. Some of these study samples, however, were not randomly selected (13,15). Based on these calculations we can be 95% confident that the differences between true proportions and observed sample proportions in the groups is <0.…”
Section: Fig 2 Histograms Showing Number Of Subjects (Percentage Ofmentioning
confidence: 99%
“…Although no significant differences between groups were found, e.g., for proportions of cesarean sections, CPD, or fetal distress, it may be that sample sizes in this study were inadequate to detect small differences. Jovanovic and Peterson (12), Frisoli et al (13), Forsbach et al (14), and Leiken et al (15) have shown that a high percentage (12-28%) of women with abnormal 50-g 1-h glucose challenge tests but normal 3-h OGTTs have babies weighing >4000 g. Some of these study samples, however, were not randomly selected (13,15). Based on these calculations we can be 95% confident that the differences between true proportions and observed sample proportions in the groups is <0.…”
Section: Fig 2 Histograms Showing Number Of Subjects (Percentage Ofmentioning
confidence: 99%
“…Studies published since the last international workshop-conference suggest that Oriental and Hispanic populations indeed may have different preva- (5), in a program of universal screening in Mexico, found a prevalence of 3.9% with the standard O'Sullivan-Mahan criteria derived for plasma. Unfortunately, 40% of patients with a positive screen failed to report for OGTT, suggesting that the true prevalence may have been greater.…”
mentioning
confidence: 99%
“…Da bei Schwangeren mit einem positiven GCT und negativem oGTT ähnlich hohe Raten an makrosomen Kindern auftreten wie bei Schwangeren bei denen beide Tests positiv sind (15,6 vs. 16,7 %) [25], erhebt sich die Frage, wozu ein 2. Test erforderlich sei.…”
Section: Vergleich Etablierter Kriterienunclassified